Analisis Potensi dan Kendala dalam Pengimplementasian Pajak Rumah Kos di Kota Kupang - Virgilia Carolina Rengga (Fakultas Ekonomi dan Bisnis, 2026)
Boarding house tax was previously implemented as one of the sources of local revenue in Kupang City before the enactment of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (HKPD), which changed the regional tax system. Although boarding houses are no longer classified as regional tax objects, the business continues to grow due to the increasing number of students and migrants requiring temporary accommodation. This study aims to analyze the potential and challenges of implementing boarding house tax in Kupang City and to identify stakeholders' perspectives on the policy. This study employed a qualitative method with a case study approach. Primary data were collected through in-depth interviews with the Regional Revenue Agency (Bapenda) of Kupang City, boarding house owners, boarding house occupants, who were predominantly university students, and representatives from academic and student affairs offices at several universities. Secondary data were obtained from relevant laws, regulations, literature, and supporting documents. Data were collected through interviews, observations, and documentation. The findings indicate that the boarding house business has considerable potential to contribute to Local Own-Source Revenue (PAD), supported by the increasing number of boarding houses, high rental demand, and the presence of universities in Kupang City. However, several challenges remain, including low taxpayer awareness, inadequate data collection and supervision, potential tax avoidance, difficulties in distinguishing boarding houses from ordinary residential houses, regulatory changes following the HKPD Law, and the potential increase in the financial burden on boarding house occupants. This study recommends improving data collection, strengthening public outreach, enhancing supervision, and promoting collaboration among stakeholders as strategic considerations for future policy development.
:: Finalisasi file repositori 20 Juli 2026_Kurnadi
Keywords: boarding house tax; potential; challenges; stakeholders; Kupang City